AN ANALYSIS OF E-BUSINESS PROCESS AT THE TOUR AND TRAVEL COMPANIES IN BANDUNG - Any Noor; Marceilla Suryana; Sholihati Amalia; Irgi Buana Putera (Tourism Scientific Journal, 2019)
The development of information technology affects rapidly in many business fields, including travel business. The number of small and medium size travel companies operating in Indonesia faces challenges with the emergence of online travel agents (OTAs), that is why business system changes must survive facing the electronic business operations (e-business). The purpose of this study is to analyze the ebusiness processes in small and medium-sized travel companies in Bandung. Analysis of the e-business process is carried out on the readiness of the technology, the readiness of the organization and the external environment. Qualitative research techniques were conducted to get accurate data. Content analysis were used on data from interviews with managers at travel companies. Respondents in this study were 5 small and medium size tourism travel companies in the city of Bandung (Bimex Tour, Binar Tour, TraveLab Polban, Segara Tour and Ranata Tour). The results showed that all travel companies in the Bandung had run businesses electronically. The company is ready in facilitating all the equipment and competent staff to operate the technology used at the company. The organization readiness shown in the commitment to provide the facilities and financial support needed to run the ebusiness process. The influence of company external factors become challenges to the company innovation to market company's products by applying available free applications. It can be concluded that small and medium size travel companies already operate electronic businesses and are able to survive in a rapid grow technology environment. Further research needs to be considered to get a complete e-business process on the side of the electronic business process with company supply chain (e-supply chain) and managing relationships electronically with consumers (E-CRM).